PENGEMBANGAN DESAIN DIDAKTIS BAHAN AJAR PERSAMAAN GARIS LURUS - Rizki Wahyu Yunian Putra; Neni Setiawati (Universitas Sultan Ageng Tirtayasa, 2018)
ABSTRACTThis study aims to produce Didaktis Design teaching materials straight line equations. This research method is Research and Development (R & D) with the model used is 4D.Tahapan done from defining phase (Define), design stage (Development), stage of dissemination (Dessiminate). Data collection techniques used are qualitative and quantitative analysis. Validation is done by material experts and media experts. The experiments were conducted through two stages: small group trial and large group trials. The results of validation of the material experts on the content quality aspect obtained an average score of 3.5 with valid criteria, on the aspect of the accuracy of the scope obtained an average score of 3.5 with valid criteria, and language aspects earned an average score of 3.2 with valid criteria. Expert media validation on Module size aspect obtains average score of 3.5 with valid criteria, skin design aspect Module obtains average score of 3.5 with valid criteria and on design aspect of content Module obtains average score 3.5 with criteria valid. In a limited trial of class VIII students in the attractiveness test obtained an average score of 3.6 with very interesting criteria and educator response with a score of 3.7 with very interesting criteria. Keywords: Dictatical Design, Development of Teaching Materials, Straight Line Equations